The influence of career development, organizational support, commitment and flexible working space against employee performance case study in East Java Indonesia - Muawanah, Roisatul; Arisyahidin, Arisyahidin; Mulyaningtiyas, Ratna Dewi (International research journal of management, IT and social sciences, 2022)
The Ministry of Finance is a vital organization for a country, how this country can develop and compete with other countries. The main indicator seen is how economic conditions are closely related to the financial structure of a country. The importance of the position of the Ministry of Finance in a country makes it must always improve its performance. This study examines the effect of career development, organizational support, commitment and flexible working space on the performance of the Ministry of Finance. The study was conducted on employees of the Ministry of Finance who are in the area of ??East Java. Data analysis using Structural Equation Modeling (SEM) with the help of Smart PLS software. The findings show that Career Development, Organizational Support, Commitment have a significant effect on Employee Performance while Flexible Working Space has no significant effect on performance. Organizations that pay attention to the career development of their employees, and provide support to employees are more likely to improve their performance compared to organizations that do not implement it. With this research, it is hoped that it can be used as a basis for formulating policies related to improving performance at the Ministry of Finance.